Dying in a foreign land: A study of completed suicides among foreign workers in Singapore. (February 2022) - Chiu, Marcus Yu Lung; Ghoh, Corinne; Wong, Christine; Wong, Kang Li
Suicide is a public health issue that impacts a nation's resident and non-resident populations alike. Singapore has one of the largest non-resident (work permit holder) populations in the world, yet very little attention has been given to examining suicide in this population. The current study examined the case materials of all 303 non-resident completed suicides in Singapore in the period January 2011 to December 2014. Their basic profiles were compared with that of the 1, 507 resident cases in the same period. A sample of 30 death notes written by non-residents were randomly selected and thematically analyzed to supplement the descriptive findings and discussion. Results showed that suicides were highest among males, those aged 21–35 years old, and South Asians. Most non-resident suicide cases did not have known physical or mental health issues, prior suicide attempts, or suicide notes. Suicide decedents from South Asia and Europe most frequently used hanging, while jumping was most common among decedents from other regions. Relationship and health problems emerged as the top two suspected triggers for suicide based on our analysis of the suicide notes. The unique situation of working abroad may increase non-residents' vulnerability in general, while adverse life events such as relationship and health issues may be too overwhelming to bear, especially when support services are not readily available and accessible. The results have implications for suicide prevention among this neglected group of people who choose to work in foreign lands.